Perception of Pharmacists as Agents of Change About the Use of Traditional Medicines by Indonesian Society - Sri Suwarni; Nurista Dida Ayuningtyas; Aris Widayati (Buletin Farmatera, 2022)
Abstract: Pharmacists, as one of the professional health workers, have a big responsibility related to the use of traditional medicines, especially pharmacists in the community who deal directly with consumers, starting from choosing to use, ensuring the safety of use, and providing education about traditional medicines. This study aims to explore the perception of pharmacists as agents of change (AoC) and whether they are ready to take an active role in Indonesian society in the use of traditional medicines. Exploratory observation is used to deepen knowledge and seek new ideas about a particular phenomenon with non-participatory observation steps. The results of this study show that many people still use traditional medicine because of the suggestions and beliefs of the community from generation to generation. Pharmacists have been able to play an active role as a source of information on conventional medicines in the community. The conclusion is that people have used a lot of traditional medicine for curing disease or trying to increase stamina, even with information on the efficacy and dosage of use according to hereditary information.